BACTERIOLOGICAL STUDY OF THROAT SWAB IN SCHOOL GOING CHILDREN: PREVALENCE OF S. HAEMOLYT1CUS AND ITS RELATION WITH RHEUMATIC FEVER - Khan, Shaheen Pervez; Khaliq, M.A.; Khan, Jahangir A. (Journal of Ayub Medical College Abbottabad, 1989)
ABSTRACT: A total of 1208 school going children in the age range 5-15 years were examined over a period of two years (1987-1990) in District Abbottabad. Streptococcal pyogen infection was 16.3%. Among them 0. 74 were suffering from Rheumatic fever.